I don't know how to solve 12x(2)-15x=0 using the quadratic equation ax+bx+c=0 with this question I am unsure of what a, b and c are supposed to be, therefore I do not know how to solve this! Please help!

  1. 0
  2. 0
  3. 1
asked by Liz
  1. The standard quadratic equation form is
    ax^2 + bx + c = 0
    and your equation is, if your (2) is supposed to be an exponent,
    12x^2 -15x = 0
    Therefore a = 12, b = -15 and c = 0

    You have reduced your equaion to
    4x^2 -5x = 0,
    so using a=4, b=-5 and c=0 would give you the same results for x.

    You should get x = 0 and x = 5/4 as the solutions, using the quadratic equation

    x = [-b +/-sqrt(b^2 -4ac)]/(2a)

    1. 0
    2. 0
    posted by drwls

Respond to this Question

First Name

Your Response

Similar Questions

  1. Algebra 2

    Factor each quadratic equation: 8x^2+10x-3 25x^2+10x-3 9x^2-15x-14 12x^2+17x-5 I don't get how to even start these! Help!
  2. algbrea

    3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -28 = 2x -12 -28 =x -40 =x 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -10x+35=63 -10x=28 x=-2.8 you are both wrong! 3x - 15x + 35 = 2x + 18 +
  3. Algebra

    Solve the quadratic equation. 3x^2-15x+18=0 I know that the formula to quadratic equation is x=-b+and-(square root)b^2-4ac divided by 2a. I know that a=3, b=-15 and c=18, then subsitute in and get two answers, my problem is that I
  4. Math

    Use the quadratic formula to solve each of the following quadratic equations... 1. 2x^2-5x=3 2. 3x^2-2x+1=0 Rearrange the equation in quadratic formula form. 2x^2 -5x -3 = 0 Then use the formula. Tell me what you don't understand
  5. 9th grade

    how do you solve the equation 15x^2-9x=12x^2+28x
  6. math

    Solve the quadratic equation. 3x^2 - 15x + 18 = 0
  7. math calculus

    (24x^3-54x^2-15x)/(6x^2-15x) i don't factor number from whole equation way i do it is find number that add to give me -54 and multiply to give -360. the number i get -60 and +6. so i do this: 24x^3-60x+6x-15x i factor this further
  8. algebra1

    could you walk-through the steps to solving this problem because I am stuck; 3x-5(3x-7)=2(x+9)+45 Let me know if you have a question in any step. 3x-5(3x-7)=2(x+9)+45 3x-15x+35= 2x+18+45 -12x+35 = 2x+63 -35 -35 -12x= 2x +63-35
  9. Algebra

    -0.2x+12x+11 solve by using quadratic equation
  10. John

    solve the quadratic equation 2x^4-3x^3-7x^2 12x-4=0

More Similar Questions